(untitled) (Research, Society and Development, 2020)
Aspiration pneumonia has great clinical importance in veterinary medicine, due to its high mortality and morbidity. In view of this fact, greater knowledge about possible causes, involved microorganisms and recommended treatments is necessary. The use of antibiotics for the treatment of aspiration pneumonia is performed empirically in most cases in veterinary medicine. Thus, the goal is identify which are the most prevalent microorganisms, as well as the most suitable antibiotics in dogs with aspiration pneumonia. A literature review was carried out with articles indexed in the scientific bases Scientific Electronic Library Online (Scielo) and PubMed, in the time frame from 1998 to 2020, using the following descriptors: “Aspiratory Pneumonia”, “Antimicrobials”, “Dogs”, "Diseases of the respiratory system". In the studies listed, the main microorganisms commonly found in aspiration pneumonia were: Mycoplasma, Escherichia coli, Pasteurella, Bordetella bronchiseptica, Staphylococcus and Streptococcus. And the most recommended antimicrobials were from the penicillin class. We conclude, then, a high prevalence of bacterial involvement in aspiration pneumonia, mainly in veterinary medicine, emphasizing the importance of knowledge about the microorganisms involved and most suitable antimicrobials.